Analisis Perbandingan Kualitas Pelayanan Pada PT. Pos Indonesia Dan J&T Express Di Tenggarong - Fatimah, Martha Trya; Erwinsyah, Erwinsyah; Akbar, Ali (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2021)
Abstract: The purpose of this study was to compare the quality of service at PT Pos Indonesia and J&T Express in Tenggarong. The problem in this research is the reality that occurs in expedition services and at PT Pos Indonesia and J&T Express in Tenggarong related to consumer complaints such as delivery of goods not on time, checking through the item tracking feature sometimes errors, lost goods during delivery, goods have physical defects when arrive at the destination, the response to consumer complaints is not well served, and so on.This study uses quantitative data obtained from questionnaire data. The number of research samples as many as 100 people using purposive sampling method. The analysis tool uses the Mann Whitney U test.Based on the results of the study indicate that there are differences in service quality at PT Pos Indonesia and J&T Express in Tenggarong. This is evidenced from the results of calculations using SPSS, the Asym Sig value on the tangible dimension is 0.000, Asymp Sig on the empathy dimension is 0.013, Asymp Sig on the responsiveness dimension is 0.001, Asymp Sig on the reliability dimension is 0.013 and Asymp Sig on the guarantee 0.000. This shows that all dimensions have Asymp sig < 0.05, so the hypothesis which states